Perancangan Interior Restoran Italia Casa Bocca di Surabaya - Jessica Novia; Gervasius Herry Purwoko; Rani Prihatmanti (Universitas Ciputra Surabaya, 2015)
The culinary business in Surabaya has been significantly developed nowadays. The lifestyle of the people in Surabaya that are prefer to dine in restaurant is one of the example of the development of the culinary business in here. There are many reasons why people would rather eat in a restaurant. In such an industrial and trading area, Surabaya, it is one of the reasons that many people need a place to relax after their busy day at work by spending their time in a restaurant or a cafe. Beside relieving fatigue and relaxing purpose, people come to restaurant for spending times with family, friends, or having a business meeting while enjoying the atmosphere.This design helps the restaurant owner to embody his desire to present the Italian nuances into the restaurant as well as create circulation that provide amenity for all the activities that happen in it.